2015
DOI: 10.1097/nne.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Education in Nursing Curricula

Abstract: Telehealth care is a fast-growing avenue of providing health care services at a distance. A descriptive study was conducted to identify trends of telehealth education in 43 schools of nursing. Findings reflected inadequate integration of telehealth in classroom content, simulation, and clinical experiences. Interviews with 4 nursing leaders of telehealth provided some recommendations on how to integrate telehealth education in nursing curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…Compared to other aspects of telehealth research (i.e., feasibility, effectiveness, economics, and satisfaction), literature related to education and training in telehealth has remained scant 14. This may be due to many providers being unacquainted with telehealth or perhaps a lack of interest in the field, secondary to this limited experience 15,16. One study found that 77% of faculty surveyed identified a need for training in telehealth 15.…”
Section: Gaps In the Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Compared to other aspects of telehealth research (i.e., feasibility, effectiveness, economics, and satisfaction), literature related to education and training in telehealth has remained scant 14. This may be due to many providers being unacquainted with telehealth or perhaps a lack of interest in the field, secondary to this limited experience 15,16. One study found that 77% of faculty surveyed identified a need for training in telehealth 15.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…This may be due to many providers being unacquainted with telehealth or perhaps a lack of interest in the field, secondary to this limited experience 15,16. One study found that 77% of faculty surveyed identified a need for training in telehealth 15. The cost of starting a telehealth program was also identified as a barrier to programmatic implementation 15.…”
Section: Gaps In the Literaturementioning
confidence: 99%
See 3 more Smart Citations